2010
DOI: 10.1084/jem.20100986
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I–deficient natural killer cells acquire a licensed phenotype after transfer into an MHC class I–sufficient environment

Abstract: In MHC class I–deficient hosts, natural killer (NK) cells are hyporesponsive to cross-linking of activation receptors. Functional competence requires engagement of a self–major histocompatability complex (MHC) class I–specific inhibitory receptor, a process referred to as “licensing.” We previously suggested that licensing is developmentally determined in the bone marrow. In this study, we find that unlicensed mature MHC class I–deficient splenic NK cells show gain-of-function and acquire a licensed phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
174
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 29 publications
(51 reference statements)
13
174
2
1
Order By: Relevance
“…5), similar to the observations of Elliot and colleagues (26). As one possible explanation, we speculate that NKG2D modulation occurs continuously as a result of interactions between NK cells and surrounding cells (43).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…5), similar to the observations of Elliot and colleagues (26). As one possible explanation, we speculate that NKG2D modulation occurs continuously as a result of interactions between NK cells and surrounding cells (43).…”
Section: Discussionsupporting
confidence: 90%
“…Using MHC class I mosaic mice, we found that mature NK cells changed their reactivity when the surrounding MHC class I setup was altered in vitro (25). More recently, two groups reported a rapid adaptation in self-reactivity of NK cells after transfer to hosts with a novel MHC class I environment (26,27). These observations are in line with our proposal that NK cell education operates like a "rheostat" that continuously tunes the NK cell activation threshold (18).…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations